2005
DOI: 10.1111/j.1741-3729.2005.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Relational Aggression in Adolescents’ Sibling Relationships: Links to Sibling and Parent‐Adolescent Relationship Quality*

Abstract: This study examined the links between sibling relational aggression and other sibling relationship qualities (i.e., intimacy, negativity, and temporal involvement) and broader parenting dynamics. Participants included 185 adolescent sibling pairs and their mothers and fathers. Data were gathered during home interviews and a series of nightly phone calls with adolescents and parents. Findings revealed that sibling relational aggression was related to sibling intimacy and negativity. In addition, connections eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 40 publications
7
60
0
4
Order By: Relevance
“…Similarly, in a longitudinal study following a Canadian sample from age 2 to 8, hostile parenting predicted membership in a trajectory group high on both indirect and physical aggression according to mothers' ratings (no trajectory group emerged for indirect aggression only; Cote, Vaillancourt, Barker, Nagin, & Tremblay, 2007). A study of adolescents' reports of relational aggression within the sibling relationship found that low parental acceptance and parental intervention in sibling conflicts were related to relational aggression between siblings, as were fathers' spending less time with siblings and fathers' favoring younger daughters (Updegraff, Thayer, Whiteman, Denning, & McHale, 2005; this study did not include a measure of relational aggression with peers). This is the first large-scale investigation to examine how authoritarian and authoritative parenting relate to social as well as physical aggression for a middle childhood sample.…”
Section: Parenting Styles and Children's Social And Physical Aggressionmentioning
confidence: 95%
“…Similarly, in a longitudinal study following a Canadian sample from age 2 to 8, hostile parenting predicted membership in a trajectory group high on both indirect and physical aggression according to mothers' ratings (no trajectory group emerged for indirect aggression only; Cote, Vaillancourt, Barker, Nagin, & Tremblay, 2007). A study of adolescents' reports of relational aggression within the sibling relationship found that low parental acceptance and parental intervention in sibling conflicts were related to relational aggression between siblings, as were fathers' spending less time with siblings and fathers' favoring younger daughters (Updegraff, Thayer, Whiteman, Denning, & McHale, 2005; this study did not include a measure of relational aggression with peers). This is the first large-scale investigation to examine how authoritarian and authoritative parenting relate to social as well as physical aggression for a middle childhood sample.…”
Section: Parenting Styles and Children's Social And Physical Aggressionmentioning
confidence: 95%
“…Immigrant siblings spent more time together, were more intimate, and provided greater social support 59,64,65 , while native born US siblings experienced greater conflict and bullying 6,7,30 . It is not yet clear how cultural differences interact with other societal characteristics, such as socioeconomic status or parenting behaviour, to affect sibling relationships 26 .…”
Section: Family Factors Associated With Sibling Bullyingmentioning
confidence: 99%
“…Child maltreatment or adult-to-child violence significantly increases the risk of sibling victimisation and bullying perpetration 6,43,45,47 . Similarly, a lack of parental warmth 59 , harsh parenting 1 , and low supervision 59,62 have also been linked with more bullying between siblings. Studies on general sibling conflict 66,67 , as well as on sibling bullying 59 , identified a link with differential parental treatment of siblings, suggesting that sibling bullying may be motivated by inequality and a desire to improve one's status, thus mimicking the motivations that underlie bullying at school 37 .…”
Section: Family Factors Associated With Sibling Bullyingmentioning
confidence: 99%
“…Furthermore, similar to physical aggression, for children in early childhood, the older sibling’s use of relational aggression predicted the younger sibling’s relational aggression towards peers (Ostrov et al, 2006). Updegraff et al, (2005) suggest that relational aggression between siblings may disrupt feelings of closeness in the sibling relationship and may be a way for children to observe and learn relational aggression. Taken together, the research on physical and relational aggression suggests that siblings have the potential to influence each other’s levels of relational and physical aggression.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, children with affect-intense sibling relationships report less behavior problems than those with relationships marked by conflict (Buist & Vermande, 2014). In contrast, displays of relational aggression are most likely to occur in the context of less emotional support and more negativity between siblings (Updegraff et al, 2005). Thus, a sibling with a high level of social skills may have a better relationship with the child, possibly resulting in less physical and relational aggression between the siblings and contributing to an overall decrease in the child’s use of aggression.…”
Section: Introductionmentioning
confidence: 99%